Knowledge and Attitude of Pharmacy Students Regarding Timing of Prescribed Medicines Administration: Chronotherapy - Humayun Mirza; Ayesha Mansoor; Farheen Ahmad; Warda Idrees; Talmeez Zeb; Amir Naveed (Pakistan Journal of Medical Research)
Objective: This study aimed to assess the awareness and attitudes towards chronotherapy among final-year pharmacy students at Lahore Medical & Dental College, providing insights into their knowledge and receptiveness to chronotherapy principles. The introduction highlights the significance of considering the optimal time for drug administration in patient care, emphasizing the impact of biological rhythms on therapeutic outcomes.